Pengaruh Penggunaan Smartphone terhadap Hasil Belajar Peserta Didik Mata Pelajaran Instalasi Penerangan Listrik - Dharma, Akbar Risky; Myori, Dwiprima Elvanny (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study aims to analyze the influence of smartphone usage on students’ academic achievement in the subject of Electrical Lighting Installation for grade XI students of the Electrical Power Installation Engineering (TITL) program at SMKN 1 Bukittinggi. The research is grounded in the increasing use of smartphones among students, most of which is for non-academic activities such as social media and gaming. This trend is suspected to disrupt students’ concentration and focus, leading to lower academic performance. The study employs a quantitative approach using surveys and documentation methods. The primary instrument is a questionnaire to assess the intensity of smartphone usage, complemented by documentation of students' learning outcomes. The analysis reveals a negative relationship between smartphone usage and student achievement. Higher smartphone usage outside of learning contexts tends to correlate with lower academic outcomes. These findings highlight the importance of monitoring and educating students on the wise use of smartphones so that technology supports learning rather than hinders it.